DESKRIPSI PROBLEM STRES KERJA DAN ALTERNATIF SOLUSINYA - Santia Agustin Banjarsari; - Yusniar (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, This study aims to find out the problems of job stress that occurs in the Education Office of Banjarmasin City and to know what factors can lead to job stress and find a good solution to overcome the problems of job stress that occurred in the office. Data analysis techbiques used in this research is data collection, data reduction, data display, and conclusion.The results of the study indicate that there are problems related to job stress in the Education Office of Banjarmasin City, the problems such as many workload problems, conflicts among employees, problems related to information technology, public complaints about schools or students, teacher-related issues, and issues outside the organization such as family issues, although the problems do not occur to all respondents and informants, only a few who claim that the problems they experienced. Factors that lead to the occurrence ot these problems are, a lot of workload, lack of human resources, differences of opinion among colleagues, employees who have not been able to apply infomation technology, and lack of time in completing the work.